2007
DOI: 10.1016/j.devcel.2006.12.002
|View full text |Cite
|
Sign up to set email alerts
|

RLE-1, an E3 Ubiquitin Ligase, Regulates C. elegans Aging by Catalyzing DAF-16 Polyubiquitination

Abstract: The forkhead transcription factor, DAF-16, a downstream target of the insulin/IGF-I signaling pathway in C. elegans, is indispensable both for lifespan regulation and stress resistance. The molecular mechanisms involved in regulating DAF-16 transcriptional activation remain undefined. Here, we have identified an E3 ubiquitin ligase, RLE-1 (regulation of longevity by E3), which regulates aging in C. elegans. Disruption of RLE-1 expression in C. elegans increases lifespan; this extension of lifespan is due to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
102
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 44 publications
5
102
0
1
Order By: Relevance
“…2B and D). This Ϸ20% change in life span is in line with the recent reports of a number of genes whose de-regulation also resulted in a similar increase of life spans (17,18).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…2B and D). This Ϸ20% change in life span is in line with the recent reports of a number of genes whose de-regulation also resulted in a similar increase of life spans (17,18).…”
Section: Resultssupporting
confidence: 78%
“…2B and D). This Ϸ20% change in life span is in line with the recent reports of a number of genes whose de-regulation also resulted in a similar increase of life spans (17,18).Several lines of evidence further support the notion that the life span extension phenotype is caused by the loss of ctbp-1. First, depletion of ctbp-1 by RNAi (Fig.…”
supporting
confidence: 74%
“…The discovery of an E3 ubiquitin ligase working through DAF16 (Li et al 2007) precipitated a thorough evaluation of the involvement of Cullin and SKR (Skp-1 related) genes in lifespan determination (Ghazi et al 2007). Although RNAi targeting of all of the Cullins and most of the SKR genes had no effect on wild-type animals' lifespan, we found that 8/21 SKR genes are significantly down-regulated during the transition to state II.…”
Section: Molecular Basis For Morphological Age Statesmentioning
confidence: 99%
“…While this study was in press, Li et al (39) published results identifying an E3 ligase that affects aging in an opposite fashion. …”
mentioning
confidence: 99%